Stem cell mobilization: methods and protocols - Klein, Gerd; Wuchter, Patrick (Methods in molecular biology, 2019)
Evolution of Peripheral Blood Stem Cell Transplantation -- In Vitro Dynamic Phenotyping for Testing Novel Mobilizing Agents -- Colony Formation: An Assay of Hematopoietic Progenitor Cells -- Mobilization and Collection of Peripheral Blood Stem Cells in Adults: Focus on Timing and Benchmarking -- Transmigration Assays for the Determination of Molecular Interactions between Hematopoietic Stem Cells and Niche Cells -- Microfluidic Shear Force Assay to Determine Cell Adhesion Forces -- A Microcavity Array-Based 3D-Model System of the Hematopoietic Stem Cell Niche -- Migration Assay for Leukemic Cells in a 3D Matrix toward a Chemoattractant -- Intravital Imaging of Blood Flow and HSPC Homing in Bone Marrow Microvessels -- Assessing Cellular Hypoxic Status In Situ within the Bone Marrow Microenvironment -- Analysis of Biomechanical Properties of Hematopoietic Stem and Progenitor Cells Using Real-Time Fluorescence and Deformability Cytometry -- Assessment of Proteolytic Activities in the Bone Marrow Microenvironment -- Analysis of the Complement Cascade Activation during Mobilization of Hematopoietic Stem/Progenitor Cells -- A Freezing Protocol for Hematopoietic Stem Cells -- Assessment of Young and Aged Hematopoietic Stem Cell Activity by Competitive Serial Transplantation Assays -- Zebrafish Xenografts for the In Vivo Analysis of Healthy and Malignant Human Hematopoietic Cells -- Statistical and Mathematical Modeling of Spatiotemporal Dynamics of Stem Cells